O queer como gesto profano em João Gilberto Noll - Sant’Anna, Evandro (2020)
Considering that João Gilberto Noll's writing animates, through almost all his fictional production, displacements of meanings regarding categories such as “body”, “sex” and “gender”, always presenting his characters from a perspective that challenges the binary limits “man/woman” and homosexual/heterosexual”, this article seeks to elaborate an analysis of Acenos e afagos (Noll, 2008c) and Berkeley em Bellagio (Noll, 2002) in the light of the concept called “profanation,” proposed by Giorgio Agamben. Here we understand the queer inscribed in the author's work as a power that, contesting the territories which literature itself is based on, is capable of profaning the discursive arbitrariness administered by the biopolitical logic that supports the contemporary arrangement.